Speech by Y.A.B. Ketua Menteri at the International Cooperative Day Celebration 1976 in the State of Penang to be held at the M.G.S. Hall Logan Road on Saturday 17th July 1976 at 2.30p.m. - Lim, Chong Eu (1976)
I wish to thank the Committee of the International Cooperative Day Celebration for 1976 in Penang fo so kindly inviting me to officiate at this celebration.